2006
DOI: 10.2215/cjn.02040606
|View full text |Cite
|
Sign up to set email alerts
|

Nephrologists’ Reported Preparedness for End-of-Life Decision-Making

Abstract: Nephrologists commonly engage in end-of-life decision-making with patients with ESRD and their families. The purpose of this study was to determine the perceived preparedness of nephrologists to make end-of-life decisions and to determine factors that are associated with the highest level of perceived preparedness. The nephrologist members of the Renal Physicians Association (RPA) and the Canadian Society of Nephrology were invited to participate in an online survey of their end-of-life decision-making practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 12 publications
7
116
0
Order By: Relevance
“…Additional help for families and caregivers is often needed as they support their loved ones through the final stages of life. Younger nephrologists tend to express less self-assessed preparedness for discussions around end-of-life issues than those with longer experience (67). In addition, in a survey of nephrology fellows, although 99% identified that it was important to provide end-of-life care, they believed that they received the least education and felt least prepared to provide this type of care (68).…”
Section: Nonaggressive Renal Care and End-of-life Carementioning
confidence: 99%
“…Additional help for families and caregivers is often needed as they support their loved ones through the final stages of life. Younger nephrologists tend to express less self-assessed preparedness for discussions around end-of-life issues than those with longer experience (67). In addition, in a survey of nephrology fellows, although 99% identified that it was important to provide end-of-life care, they believed that they received the least education and felt least prepared to provide this type of care (68).…”
Section: Nonaggressive Renal Care and End-of-life Carementioning
confidence: 99%
“…For example, while patients with ESRD prefer to be given information about their prognosis by their physicians and those who participate in end-of-life discussions tend to prefer less aggressive care, few dialysis patients report having had even limited discussions about their wishes (28,(32)(33)(34). The dearth of discussions is likely fueled by provider uncertainty about prognosis and a lack of attention during training (35)(36)(37). However, reliable instruments have been developed to identify dialysis patients at highest risk of death, and fellowship training programs have been encouraged to attend more to building this skill (36,38,39).…”
Section: Barriers To a Palliative Approach To Dialysis Provider Barriersmentioning
confidence: 99%
“…There are, however, several challenges to true informed consent and shared decision-making. First, nephrologists and nephrology fellows have reported that they feel ill-prepared to have these discussions (67,68). Second, physicians often bring their biases to the bedside, which can affect the patients' perception and ultimate decision (51,69).…”
Section: Shared Decision-making As An Answer To the Ethical Challengesmentioning
confidence: 99%